Development of a water solubility model of extruded feeds by utilizing a starch gelatinization model. Issue 1 (31st December 2022) - Cheng, Hongyuan; Wang, Hao; Ma, Shifeng; Xue, Min; Li, Junguo; Yang, Jie
ABSTRACT: This study aimed to estimate the effects of extrusion variables on extruded aquafeed water solubility using a starch gelatinization model. A new equation was derived from a classical starch gelatinization degree model to calculate aquafeed water solubility. After considering the data of five formulations, the average absolute deviation (AAD) of the new equation was 7.97% for the extrudate water solubility and 2.24% for the water solubility index. In the most cases, water solubility and water solubility index increased with an increase in the process screw speed and temperature but decreased with a decrease in water content. On the other hand, when the moisture content increased from 0.2 to 0.3 kg/kg, the water solubility increased from 4.91 to 5.22% (wt) for a typical recipe in the low moisture content extrusion process. The new equation established a way to quantitatively elaborate the relationship between the extrudate water solubility and extrusion process variables.